Endothelial cell apoptosis induced by bacteria-activated platelets requires caspase-8 and -9 and generation of reactive oxygen species - Kuckleburg, Christopher J; Tiwari, Raksha; Czuprynski, Charles J (Thrombosis and haemostasis, 2008)
A common feature of severe sepsis is vascular inflammation and damage to the endothelium. Because platelets can be directly activated by bacteria and endotoxin, these cells may play an important role in determining the outcome of sepsis. For example, inhibiting platelet interactions with the endothelium has been shown to attenuate endothelial cell damage and improve survival during sepsis. Although not entirely understood, the interactions between bacteria-activated platelets and the endothelium may play a key role in the vascular pathology of bacterial sepsis. Haemophilus somnus is a bacterial pathogen that causes diffuse vascular inflammation and endothelial damage. In some cases H. somnus infection results in an acute and fatal form of vasculitis in the cerebral microvasculature known as thrombotic meningoencephalitis (TME). In this study, we have characterized the mechanisms involved in endothelial cell apoptosis induced by activated platelets. We observed that direct contact between H. somnus-activated platelets and endothelial cells induced significant levels of apoptosis; however, Fas receptor activation on bovine endothelial cells was not able to induce apoptosis unless protein synthesis was disrupted. Endothelial cell apoptosis by H. somnus-activated platelets required activation of both caspase-8 and caspase-9, as inhibitors of either caspase inhibited apoptosis. Furthermore, activated platelets induced endothelial cell production of reactive oxygen species (ROS) and disrupting ROS activity in endothelial cells significantly inhibited apoptosis. These findings suggest that bacterial activation of platelets may contribute to endothelial cell dysfunction observed during sepsis, specifically by inducing endothelial cell apoptosis.